Exploring the protease diversity of psychrophilic yeast, glaciozyma antarctica through genome mining analysis - Norfarhan Mohd-Assaad,; Rohaiza Ahmad Redzuan,; Mohd Faizal Abu Bakar,; Nor Muhammad Mahadi,; Abdul Munir Abdul Murad,; Rosli Md. Illias,; Quay, Doris Huai Xia; Izwan Bharudin,; Farah Diba Abu Bakar,; Shazilah Kamaruddin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Proteases are one of the most significant classes of enzymes, holding immense physiological relevance and extensive industrial applications. The genome of Glaciozyma antarctica was fully sequenced, showing 7,857 open reading frames that offer an intriguing opportunity to investigate its proteolytic repertoire. This study aims to unveil the protease landscape of G. antarctica, a psychrophilic yeast that produces cold-active enzymes that offer remarkable benefits, particularly in the food and pharmaceutical industries. In this work, we performed a comprehensive analysis to identify the diverse families of proteases encoded within the G. antarctica genome and compare them with proteases from other mesophilic and thermophilic fungi in the MEROPS database. The sequence similarity searches resulted in the identification of 195 open reading frames predicted to encode for proteases in G. antarctica with a high number of intracellular proteases. These findings suggest an evolved system for protein quality control and turnover, essential for cell viability and adaptation to environmental stressors. The MEROPS classification analysis showed an abundance of metalloproteases, constituting 38% of the total protease genes, a proportion surpassing that found in other yeast and fungal genomes studied. This reflects the vital role of metalloproteases in the cold adaptation of microbes in the Antarctic region. This unique profile not only sheds light on the adaptive mechanisms of psychrophilic organisms but also presents a rich reservoir of potential cold-active proteases for various applications. The findings of this study provide a foundation for targeted enzyme discovery and engineering, unlocking new frontiers in industrial biotechnology and extremophile biology.